1992
DOI: 10.1128/aac.36.10.2192
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of oral teicoplanin versus oral vancomycin for therapy of pseudomembranous colitis and Clostridium difficile-associated diarrhea

Abstract: A prospective, randomized study comparing oral teicoplanin with oral vancomycin in the treatment of pseudomembranous colitis (PMC) and Clostridium djffcile-associated diarrhea (CDAD) was performed.Teicoplanin was administered at a dosage of 100 mg twice a day for 10 days, and vancomycin was administered at a dosage of 500 mg four times a day for 10 days. CDAD was diagnosed by demonstrating both C. dfficile and cytotoxin in the feces of symptomatic patients (more than three loose stools per day). The diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(68 citation statements)
references
References 38 publications
2
64
0
2
Order By: Relevance
“…The most common limitations of trial design included lack of blinding of study participants, and the absence of testing of the adequacy of blinding and allocation concealment. Of the nine included trials four were double-blinded, 14,17,18,21 three trials did not report the blinding status 15,16,20 and two trials were randomized but had no concealment of allocation. 19,22 There was considerable variation in the extent to which the colonic mucosa was assessed in the included trials.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common limitations of trial design included lack of blinding of study participants, and the absence of testing of the adequacy of blinding and allocation concealment. Of the nine included trials four were double-blinded, 14,17,18,21 three trials did not report the blinding status 15,16,20 and two trials were randomized but had no concealment of allocation. 19,22 There was considerable variation in the extent to which the colonic mucosa was assessed in the included trials.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…with either teicoplanin 50 mg q.d.s. 21 or vancomycin 500 mg q.d.s., 20 and one trial directly compared vancomycin, metronidazole, teicoplanin and fusidic acid. 22 The outcome data are summarized in Tables 2 and 3.…”
Section: Search Strategymentioning
confidence: 99%
“…Few studies, which analysed the use of oral teicoplanin in the treatment of CDI, showed its success [7,8]. The achieved clinical cure rates were 96% and 96.2%, while recurrence rates were 7% and 7.7% [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous tygecyclin, intravenous immunoglobulins, oral vancomycin in higher doses, and vancomycin enema are some of the suggested treatment regimens but they were all applied to a small number of patients [3][4][5][6]. Oral teicoplanin is another antibiotic, which was proven to be successful in the treatment of patients with CDI, including those with severe disease [7,8]. Previous studies have not analysed the role of teicoplanin in the treatment of refractory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for recurrences may follow vancomycin administration in a pulsed regimen (Mc Farland et al, 2002) that allows the germination of spores in between antimicrobial administration to improve efficacy. Other antibiotics, nitazoxanide, teicoplanin and most recently fidaxomicin h a v e b e e n s h o w n t o b e a s e f f e c t i v e a s vancomycin treatment and have been indicated as possible alternative therapies (de Lalla et al, 1992 ;Louie et al;Musher et al, 2009). …”
Section: Antimicrobial Therapymentioning
confidence: 99%